Impact of simulated knee injuries on the patellofemoral and tibiofemoral kinematics investigated with an electromagnetic tracking approach: A cadaver study - Rath, Bjoern; Asseln, Malte; Betsch, Marcel; Prescher, Andreas; Tingart, Markus; Eschweiler, Joerg (BioMed Research International, 2018)
Purpose. The purpose of this study was to evaluate the approach of using an electromagnetic tracking (EMT) system for measuring the effects of stepwise, simulated knee injuries on patellofemoral (PF) and tibiofemoral (TF) kinematics. Methods. Three cadaver knees were placed in a motion rig. EMT sensors were mounted on the patella, the medial/lateral femoral epicondyles, the tibial condyle, and the tibial tuberosity (TT). After determining the motion of an intact knee, three injuries were simulated and the resulting bony motion was tracked. Results. Starting with the intact knee fully extended (0° flexion) and bending it to approximately 20°, the patella shifted slightly in the medial direction. Then, while bending the knee to the flexed position (90° flexion), the patella shifted progressively more laterally. After transecting the anterior cruciate ligament (ACL), the base of the medial menisci (MM) at the pars intermedia, and the medial collateral ligament (MCL), individual changes were observed. For example, the medial femoral epicondyle displayed a medial lift-off in all knees. Conclusion. We demonstrated that our EMT approach is an acceptable method to accurately measure PF joint motion. This method could also enable visualization and in-depth analysis of in vivo patellar function in total knee arthroplasty, if it is established for routine clinical use.
CRIS-Team Scopus Importer:2022-07-20